Optimasi penjadwalan menggunakan program linear - Rahmawati, Elif Thoyyibah (Maliki Interdisciplinary Journal, 2026)
This study examines the application of linear programming as an optimization method for university course scheduling. Academic scheduling problems are often complex due to the involvement of multiple interrelated components such as courses, lecturers, classrooms, and time slots, each with specific constraints. Therefore, a systematic mathematical approach is required to minimize conflicts and improve resource utilization. The linear programming model is constructed using binary decision variables to represent whether a course is assigned to a specific time slot. The objective function is designed to minimize scheduling conflicts and maximize the efficiency of resource usage, while the constraints reflect real-world conditions, such as preventing lecturer conflicts, avoiding overlapping classroom usage, and ensuring each course is scheduled only once. Simulation data are used to test the developed model. The results indicate that linear programming successfully produces structured, conflict-free, and efficient schedules compared to manual methods. Thus, this approach can serve as an effective solution for improving scheduling systems in educational institutions and supports more rational and systematic decision-making processes.